The Challenges in Implementing Vietnam’s Nationally-Determined Contribution (NDC) in the Agriculture Sector under the Current Supporting Laws, Regulations, and Policies - Duc Trung, Nguyen; Le Hoang Anh; Nguyen Trung Thang; Sebastian, Leocadio S. (2018)
This study reviews the current supporting laws, regulations, and policies in Vietnam and their applicability in the effective implementation of Nationally Determined Contributions (NDC) agriculture activities in Vietnam. The Ministry of Agriculture and Rural Development (MARD) is responsible for the development of NDC activities for the agricultural sector. It can be noted that there is a strong supporting legal framework in Vietnam. There are, however, some challenges and gaps that could potentially affect the effective implementation of NDC activities in agriculture. The study considered the following five areas as critical to NDC implementation: 1) awareness and technical capacity; 2) implementation coordination; 3) downscaling to the provinces; 4) engagement of private sector and NGOs; and 5) regulatory framework. Some recommendations are proposed on how to address the challenges in the five areas identified.